Research priorities to improve the health of children and adults with dysphagia: a National Institute of Health Research and Royal College of Speech and Language Therapists research priority setting partnership. Issue 1 (25th January 2022) - Pagnamenta, Emma; Longhurst, Lauren; Breaks, Anne; Chadd, Katie; Kulkarni, Amit; Bryant, Val; Tier, Kathy; Rogers, Vanessa; Bangera, Sai; Wallinger, Josephine; Leslie, Paula; Palmer, Rebecca; et al.
Abstract : Objective: To conduct the first UK-wide research priority setting project informing researchers and funders of critical knowledge gaps requiring investigation to improve the health and well-being of patients with eating, drinking and swallowing disorders (dysphagia) and their carers. Design: A priority setting partnership between the National Institute of Health Research (NIHR) and the Royal College of Speech and Language Therapists using a modified nominal group technique. A steering group and NIHR representatives oversaw four project phases: (1) survey gathering research suggestions, (2) verification and aggregation of suggestions with systematic review research recommendations, (3) multistakeholder workshop to develop research questions, (4) interim priority setting via an online ranking survey and (5) final priority setting. Setting: UK health services and community. Participants: Patients with dysphagia, carers and professionals who work with children and adults with dysphagia from the UK. Results: One hundred and fifty-six speech and language therapists submitted 332 research suggestions related to dysphagia. These were mapped to 88 research recommendations from systematic reviews to form 24 'uncertainty topics' (knowledge gaps that are answerable by research). Four patients, 1 carer and 30 healthcare professionals collaboratively produced 77 research questions in relation to these topics. Thereafter, 387 patients, carers and professionals with experience of dysphagia prioritised 10 research questions using an interim prioritisation survey. Votes and feedback for each question were collated and reviewed by the steering and dysphagia reference groups. Nine further questions were added to the long-list and top 10 lists of priority questions were agreed. Conclusion: Three top 10 lists of topics grouped as adults, neonates and children, and all ages, and a further long list of questions were identified by patients, carers and healthcare professionals as research priorities to improve the lives of those with dysphagia.